2022
DOI: 10.3390/ani13010094
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an Undescribed Babesia sp. in Capybaras and Amblyomma Ticks in Central-Western Brazil

Abstract: Capybaras (Hydrochoerus hydrochaeris) are the largest rodents on Earth. While capybaras are hosts for various tick species, there is limited information regarding the tick-borne pathogens they can carry. We investigated the presence of piroplasmids and Ehrlichia spp. in capybaras and their associated ticks in two peri-urban areas in Goiás state, central-western Brazil. Blood samples collected from 23 capybaras were used to investigate the presence of piroplasmids and Ehrlichia spp. in stained-blood smears and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Once trapped and physically restrained with the net, capybaras were anesthetized with an intramuscular injection of ketamine (10 mg/kg) plus xylazine (0.5 mg/kg). Capybaras were identified with a subcutaneous microchip (Allflex), clinically monitored during the procedure until recovery from anesthesia, and released at the same capture site, as suggested by Neves et al [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Once trapped and physically restrained with the net, capybaras were anesthetized with an intramuscular injection of ketamine (10 mg/kg) plus xylazine (0.5 mg/kg). Capybaras were identified with a subcutaneous microchip (Allflex), clinically monitored during the procedure until recovery from anesthesia, and released at the same capture site, as suggested by Neves et al [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although South America is not considered to be endemic for zoonotic Babesia spp., which have not been reported in wild animals so far, the circulation of competent tick vectors for other Piroplasmida species that can parasitize domestic and wild animals emphasizes the need for constant surveillance [ 1 ]. In this sense, some studies have pointed out the participation of wild animals, such as the capybara ( Hydrochoerus hydrochaeris ), the largest rodent in the world, in the life cycle of piroplasmids and/or associated ticks, such as Amblyomma sculptum and Amblyomma dubitatum [ 5 ]. Since capybaras are hosts for A. sculptum ticks and amplifying hosts for Rickettsia rickettsii , the agent of Brazilian spotted fever, understanding the role of these rodents as hosts for other microorganisms is important [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twelve years later, Gonçalves et al [ 9 ] reported the presence of Piroplasmida partial 18S rRNA sequences, showing >97% identity with the previously reported capybara-associated piroplasmid [ 8 ] in a female and a nymph of A. dubitatum , collected from a capybara and a black rat ( Rattus rattus ), respectively, in the state of Mato Grosso do Sul. In the state of Goiás, central-western Brazil, Neves et al [ 5 ] reported the presence of capybara-associated Babesia sp. DNA in capybaras and two female ticks of A. sculptum and A. dubitatum .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations